The Representation of Politics in Andrea Hirata’s Novel Laskar Pelangi: A Social, Cultural, and Applied Linguistic Analysis - Muhammad Natsir Amir; Zuriyati; Miftahulkhairah; Yasir Riady; Muhammad Ajmal (CV Media Inti Teknologi, 2025)
Background of study: The novel reveals real social inequalities, where access to quality education remains a privilege for a few, while children from underprivileged backgrounds must contend with various limitations, from inadequate school facilities to difficult family economic conditions. Aims and scope of paper: This research explores the representation of politic in the novel Laskar Pelangi by Andrea Hirata through a social and cultural analysis approach. This novel is a medium for depicting fundamental issues in Indonesian society, such as inequality in access to education, economic injustice and exploitation of natural resources Methods: This research uses qualitative methods with a descriptive-analytical approach to explore political, social and cultural meanings in the text. Result: The results of the analysis show that Laskar Pelangi not only criticizes educational policies and socio-political dynamics, but also inspires readers to reflect on the role of literature in voicing social change. In this way. Conclusion: This novel is a reflection of the complexity of Indonesian society as well as a tool for social criticism that is relevant in the study of political and cultural literature.